Cancer in rural America: Improving access to clinical trials and quality of oncologic care - Joseph M. Unger; Barbara L. McAneny; Raymond U. Osarogiagbon (CA: A Cancer Journal for Clinicians, 2025)
Abstract Individuals from rural areas in the United States suffer higher rates of morbidity and mortality from cancer than their urban counterparts. This review is based on the idea that equity—the elimination of unnecessary and preventable differences between groups of individuals—should underlie access to cancer care resources for patients from rural areas. Access to cancer clinical trials serves as the framework for identifying and understanding barriers in access to quality oncologic care. The authors discuss the interplay between rural living, socioeconomic status, culture, and health; and they highlight how economic considerations in rural areas often limit access to clinical trials and oncologic care because economies of scale do not apply in these regions given the requirement for high‐quality oncology care even with lower patient volumes. The authors propose solutions to enhance access to clinical trials and improve the quality of oncologic care in rural areas, viewing these aims as ethical and moral imperatives.